Wind Bands for Hungarian Community Music - Radócz, Miklós (Central European Journal of Educational Research, 2021)
The scholarly study of community bands as music communities can be considered a relatively young trend even on an international level. Despite this fact, there is more and more research done on the potential effects they may have on society and music education. Our national literary records on wind bands, however, are mainly focused on their historical background and their legacy in the military. Thus, there is an insufficient amount of information provided on the aspects of sociology and pedagogy. Besides the literary comparison done in our research, we also study the resupply of our national bands in music schools, using available data from the the 2016/2017 Statistical Yearbook of Public Education. This paper serves mainly as a tool of problem identification, laying the groundwork for further researches done in this area.